The Ex Vivo Effect of Preadsorbed Vitronectin on Platelet Activation - Fabrizius-Homan, D J; Cooper, S L; Mosher, D F (Thrombosis and Haemostasis, 1992)
The activation of ex vivo canine platelets by preadsorbed vitronectin (VN) was sensitive not only to the polymer substrate utilized but also to the adsorption conditions employed. Lower levels of maximal platelet deposition were obtained for VN-coated silicone rubber (SR) than for other VN-coated substrates with comparable levels of adsorbed VN, but this effect was diminished with increased residence time of VN on the SR surface. Submonolayer and monolayer surface concentrations of VN elicited similar maximal levels of platelet deposition at both short (<3 h) and long (>12 h) residence times, but thrombi were larger and more dense for the submonolayer surface concentrations. VN was also more effective in forming thrombi when adsorbed sequentially before albumin instead of after albumin. To further examine these differences in the nature of adsorbed VN between substrates and adsorption conditions, sodium dodecyl sulfate (SDS) elutability measurements and Fourier transform infrared spectroscopy with attenuated total reflectance optics (FTIR-ATR) evaluations of the adsorbed protein were performed. An SDS solution was able to remove a greater percentage of the VN which was adsorbed to a submonolayer than a monolayer surface concentration when SDS displacement was initiated immediately after adsorption was terminated. However, if the adsorbed protein was allowed to reside on the surface for a length of time before the introduction of the SDS displacing media, a greater percentage of the monolayer surface concentration was removed. The submonolayer surface concentration may be better able to increase its strength of contact with the surface during the added residence time than the monolayer surface concentration. FTIR-ATR spectra of VN showed less structural alterations when it was adsorbing to SR than to a segmented polyurethane, a more thrombogenic material when coated with VN. Thus, the ability of VN to stimulate thrombus formation appeared to correlate with the percentage of VN which was nonelutable by SDS and the amount of structural alterations observed by FTIR-ATR, both of which are indications of its extent of contact with the surface.